Psycholinguistic evidence for split intransitivity in Spanish second language acquisition - MONTRUL, SILVINA (Applied psycholinguistics, 2004)
This study investigates the acquisition and on-line processing of unaccusative and unergative verbs in second language (L2) Spanish by English-speaking learners. It asks whether L2 learners make a syntactic distinction between the two verb classes and whether there is an effect of semantic subclass, in accordance with a semantic hierarchy. Participants were 35 native Spanish speakers and 44 English-speaking learners of Spanish ranging from intermediate to advanced proficiency. The main task was an on-line visual probe recognition task. Subjects read sentences on a computer screen and had to decide whether a word had appeared in the sentence. The results of this study showed that native speakers who scan their syntactic representations to find a word contained in a complex subject noun phrase recognized the word faster with unaccusative-verb sentences than with unergative-verb sentences, suggesting that the syntactic presence of a trace in unaccusative-verb sentences facilitates comprehension. The L2 learners showed a similar response pattern, confirming that they differentiated between the two classes of verbs. Analyses of reaction times by verb class indicated that not all of the verbs in each class were responded to consistently: some subclasses induced shorter reaction times than others.